PKM Urgensi Literasi dan Numerasi di Pendidikan Dasar - Lestari, Nyoman Ayu Putri; Sudewiputri, Made Padmarani; Diputra, I Gusti Agung Putu Sagung Angga; Mekarini, Ni Wayan (Synergy and Society Service, 2025)
This community service program aims to improve literacy and numeracy skills among elementary school students. This activity was carried out at SD Negeri 1 Tegal Badeng Barat, which faced challenges in mastering reading, writing and arithmetic skills. Through an interactive and fun approach, this program organizes various activities, such as reading training, educational games, and numeracy workshops. The involvement of parents and teachers is also a focus to create a supportive learning environment. Thus, this service not only improves students' academic abilities, but also grows their interest in learning. The results of this activity showed a significant increase in participants' literacy and numeracy skills, as well as an increase in interest in reading and learning. Apart from that, this program also builds public awareness of the importance of literacy and numeracy as the foundation of strong education. It is hoped that this initiative can continue and provide a sustainable positive impact on developing community capacity. The hope for the future is to continue this program on an ongoing basis and expand its reach to other schools.